Lean in : women, work, and the will to lead - Sandberg, Sheryl; Scovell, Nell. (New York : Alfred A. Knopf, 2013)
In "Lean In", Sheryl Sandberg -- Facebook COO and one of "Fortune" magazine's most powerful women in business -- looks at what women can do to help themselves, and make the small changes in their life that can effect change on a more universal scale. She draws on her own experiences working in some of the world's most successful businesses, as well as academic research, to find practical answers to the problems facing women in the workplace.
Internationalizing the revolution -- The leadership ambition gap : what would you do if you weren't afraid? -- Sit at the table -- Success and likeability -- It's a jungle gym, not a ladder -- Are you my mentor? -- Seek and speak your truth -- Don't leave before you leave -- Make your partner a real partner -- The myth of doing it all -- Let's start taking about it -- Working together toward equality -- Let's keep talking.
Includes bibliographical references (pages [183]-217) and index.
Keywords: Sandberg, Sheryl; Women executives; Leadership in women